A Very Rare Case of Colpocephaly Associated With Trisomy 18 - Seyfettin Uludağ; Yavuz Aydın; Begüm Aydoğan; Burcu Aydın (Medical Network, 2012)
We presented a very rare case of colphocephaly which is a term used to describe a congenital abnormal enlargement of the occipital horns of the lateral ventricules associated with normal frontal horns. A variety of cranial abnormalities and syndromes were associated with colphocephaly such as such as lissencephaly type 1, linear nevus sebaceous syndrome, Marden-Walker syndrome, tourette syndrome, Aicardi syndrome, trisomy 8 mosaic, trisomy 9 mosaic, Norman-Roberts syndrome, Zellweger syndrome, Nijmegen breakage syndrome, hemimegalencephaly, Chudley-McCullough syndrome; but association of colphocephaly with trisomy 18 case has not been identified up to now.